Qualitative Analysis of Questionnaire Results to Clarify Local Community's Negative Stigma Towards Mount Kemukus - Dwi Ari Septyowati; Budi Waluyo; Astiana Ajeng Rahardini (Britain International for Academic Research (BIAR) Publisher, 2025)
This research aims to clarify the negative stigma of the local community that develops towards the Mount Kemukus Tourism Object. This study uses a qualitative descriptive method. The data collection technique used a questionnaire in the form of a google form involving 50 respondents from 11 villages in Sumberlawang District. The results of the study show that there is still a negative stigma of the local community towards the Mount Kemukus Tourism Object, especially in its pilgrimage rituals. The community believes that there are irregularities in the ritual of blessing ngalap berber. Deviations in the form of sexual intercourse with a non-halal partner which is part of the pilgrimage ritual to the Tomb of Prince Samodra or the Wsata Object of Mount Kemukus. The existence of this negative stigma makes Mount Kemukus Tourism Object famous because it reaches foreign countries. This is a concern for the Sragen Regency Government.